(untitled) (International Journal of Engineering and Computer Science, 2013)
This project is a step towards the preventative healthcare for cardiac patients. It seeks to develop a smart mobile ECG monitoring system that continuously monitors what is happening around the subject when an arrhythmia event occurs. The problem we are facing now is the unexpected death of our loved ones because of the sudden heart attack. Because of the changing life style the heart attack rate is increasing day by day. The current heart attack death rate is about 25% of the total deaths in India. The main cause of heart attack death is the lack of medical care at the right time. This problem can be avoided by this project. Here I am presenting an android based portable ECG monitor. The patient will be wearing a small device which senses the ECG data. It will send the sensed data to the patient’s Android mobile through Bluetooth. The Android mobile will be having an application which will be running a heart attack detection algorithm. If any abnormalities are found the patient will be notified through an audible alarm and first aid techniques will be shown to the patient in the phone’s display. This first aid instruction will increase the chance of survival of the patient. A report of the ECG will be send to the patient’s doctor through email so that he can prepare himself for the treatment. And also a sms containing patient’s location (gps data) will be send to the hospital so that help can be given at the earliest even if the patient is travelling. The goal is to provide early heart attack detection so that the patient will be given medical attention within the first few critical hours, thus greatly improving his or her chances of survival